Workforce diversity and employee job satisfaction: Mediating role of organizational climate in the hospitality sector in Kerala - Mohammad, Suleiman Ibrahim Shelash; Joseph, Regy; Raja, N; Jegadeeswari, S; Vasudevan, Asokan (International Journal of Innovative Research and Scientific Studies, 2025)
Workforce diversity is central to the function of any organization in the 21st century. The workforce is increasingly becoming a mix of individuals from different groups of society. These groups of people from different races, genders, ethnicities, religions, ages, and abilities are forming today’s workforce. Job satisfaction is a complex set of attitudes about different factors related to the job. Despite the controversies, there are certain common elements that emerge from most understandings: the psychological or emotional changes in people as their level of satisfaction changes, and emotional responses directed towards the employed staff or the job they perform in work settings. Organizational climate, like company culture, is a business’s personality. Organizational climate is the result of the company’s structure, leadership style, and strategic goals. Climate is represented by a number of characteristics, including sincere respect for people, minimal governance, and the use of consultative decision-making methods. The present study is an attempt to provide important research findings from the Indian hospitality industry, focusing on the likely influence of various challenges of workplace diversity on employee job satisfaction. The unique contribution of the study lies primarily in identifying the individual mediating function of organizational climate between workplace diversity and employee job satisfaction. A structured questionnaire was used to collect primary data for the present study, and the study can be characterized more as a quantitative study. The questionnaires were handed out to various groups of employees and their supervisors working in different hotels in the hospitality sector in Kerala. It was found that there exists a positive relationship between workforce diversity and employee job satisfaction in the hotel industry in Kerala.